2017
DOI: 10.24818/jamis.2017.04004
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the CSR and the accounting information system data in Central and Eastern European (CEE) countries – the evidence of the Polish financial institutions

Abstract: Financial institutions play a fundamental role in determining the sustainability of economies, both in developed and developing countries. However, the worldwide financial crises made many financial institutions lost their credibility and CSR engagement has been perceived as a remedy. The aim of this paper is to analyze the interrelation between being socially responsible and tangible financial outcome of financial institutions in one of the CEE countries -Poland. Financial and market data of all the public co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
6
0
4
Order By: Relevance
“…Earlier papers [15,32] did not control for an endogeneity problem, as they used a data set from different countries that includes the period of crisis, as well as pre-crisis or post-crisis periods. Some research to avoid this endogeneity problem partially investigated the relationship between CSR and FP before the crisis [22,44] after the crisis [52], or around the crisis [53]. The scope of this study did not exclude the crisis period, so to limit the impact of the financial crisis on the CSR and FP relationship, we focused on banks that were not significantly affected by the crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier papers [15,32] did not control for an endogeneity problem, as they used a data set from different countries that includes the period of crisis, as well as pre-crisis or post-crisis periods. Some research to avoid this endogeneity problem partially investigated the relationship between CSR and FP before the crisis [22,44] after the crisis [52], or around the crisis [53]. The scope of this study did not exclude the crisis period, so to limit the impact of the financial crisis on the CSR and FP relationship, we focused on banks that were not significantly affected by the crisis.…”
Section: Introductionmentioning
confidence: 99%
“…The in-depth analysis of literature in terms of confirming indicated hypotheses (e.g., [46]) reveals that although many academics tried to empirically analyze the relation between CSR and CFP, the results of their works are neither coherent nor definite, and with no consensus. The results have often been contradictory, even within a given analysis [45] (p. 6).…”
Section: Heterogeneity Of Relation Between Corporate Social-environmementioning
confidence: 99%
“…Moreover, these different approaches of CSR are combined with various types of CFP indicators that are based on accounting measures (like return of equity, return of assets, return of sales, current ratio, relation debt/equity, relation EBIT to interest expense, total assets, EPS) and on market-based measures (like Alpha, Beta, relation price to earnings, capital adequacy ratio, mean abnormal returns, risk adjusted return, stock price, relation market value to book value). A combination of these different approaches of CSR and CFP results in multitude of diverse applications and the results of empirical analyses [46] (p. 499).…”
Section: Heterogeneity Of Relation Between Corporate Social-environmementioning
confidence: 99%
“…They suggested that effective cooperation between the public and private sectors and NGEOs (Non-governmental Environment Organisations) is essential to address the most pressing social challenges of developing societies [23]. CSR research was performed by [24] in the countries of Central and Eastern Europe in the financial sector. Based on the comparative analysis, a conclusion was made that there is a significant difference in CSR issues between the countries of Central and Eastern Europe and many Western economies.…”
Section: Corporate Social Responsibility (Csr)mentioning
confidence: 99%